The Dual Impact of Artificial Intelligence Technologies on the Crime of Genocide - Abdul Qader, Raneen (Journal of Legal Sciences, 2026)
The dual impact of artificial intelligence (AI) on genocide lies in its potential to serve either as a tool for preventing mass atrocities or as a means to facilitate their commission. On the one hand, AI can contribute to the early detection of genocide indicators through big data analysis, monitoring hate speech, and identifying patterns of violence before they escalate. AI has become a modern field of global interest, as it is expected to play a significant role in the future of humanity. It focuses on designing machines that exhibit intelligent behavior similar to humans, enabling the international community to intervene to prevent crimes. By employing machine learning techniques, AI can accurately document violations and collect forensic evidence to support international justice. While new technologies and modern technical applications offer numerous advantages—saving time and effort, reducing costs, and increasing efficiency—they also carry significant risks. AI poses considerable dangers when used in international crimes, as it could target human groups without direct human supervision, thereby undermining the principle of legal accountability. Furthermore, AI applications may be exploited for propaganda or to identify vulnerable minority groups through the analysis of large-scale digital data. Thus, AI represents a double-edged sword: while it can enhance human security and prevent international crimes, it can also become a powerful tool for committing them if misused or left without clear legal regulations.